Features of media and journalistic orientation in the writings of Al-Jahiz - derbali, wahiba (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
The present paper discusses the contributions of Al-Jahiz in the field of journalistic writing by presenting his concepts and key opinions that fall within the realm of journalistic rhetoric. The traces of journalistic editing emerged in Al-Jahiz’s writings, where he employed writing techniques that closely resembled those employed in journalistic articles with a modern touch. Al-Jahiz focused on the theme of communication in his literary works, connecting it to the process of understanding. He emphasized the communicative function and gave it special attention over other literary functions. Al-Jahiz’s creativity lies in his ability to link rhetorical discourse with the elements of communication, working on the processes of comprehension and conveying he dedicated to the theoretical aspect of rhetorical communication.